Prediksi Jumlah Angka Kemiskinan di Kabupaten Deli Serdang Tahun 2024 (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Poverty is one of the main problems that hinder regional development. Deli Serdang Regency shows a fluctuating trend in the number of poor people from year to year. To support government policies in overcoming poverty, an accurate forecasting method is needed to predict the number of poor people in the future. This study uses the Single Moving Average (SMA) method with two period variations, namely n = 2 and n = 3, based on data from the Central Statistics Agency (BPS) of Deli Serdang Regency for 2017–2023. The forecasting results show that the SMA method with n = 3 provides better accuracy than n = 2, as indicated by the Mean Squared Error (MSE) value of 21.38, Mean Absolute Deviation (MAD) of 4.44, and Mean Absolute Percentage Error (MAPE) of 3.52%. These findings indicate that the SMA method is capable of providing fairly accurate predictions and can be used as a basis for regional development policy planning to reduce poverty in Deli Serdang Regency in 2024.